2011
DOI: 10.4012/dmj.2011-057
|View full text |Cite
|
Sign up to set email alerts
|

Wear simulation effects on overdenture stud attachments

Abstract: The aim of this study was to evaluate wear effects on overdenture resilient attachments. Six commercially available attachments were investigated: ERA orange and white (EO and EW), Locator pink, white and blue (LRP, LRW and LRB) and OP anchor (OP). Five specimens were used for wear simulation while other two specimens served as controls. Fifteen thousands insertion-removal cycles were simulated. Dimensional changes and surface characteristics were evaluated using light microscopy and SEM, respectively. Sudden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
139
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(170 citation statements)
references
References 19 publications
(21 reference statements)
25
139
1
5
Order By: Relevance
“…This finding was not surprising, and in accordance with previous in vitro investigations . The retention loss can be described by wear and degradation of the nylon components during loading; however, it seems that degradation of the inserts does not necessarily produce a proportional deterioration in retention, as it may increase surface roughness and produce a corresponding increase in retention through micromechanical friction . This may explain the increased retention of Lm on 20° angled implants after wear simulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding was not surprising, and in accordance with previous in vitro investigations . The retention loss can be described by wear and degradation of the nylon components during loading; however, it seems that degradation of the inserts does not necessarily produce a proportional deterioration in retention, as it may increase surface roughness and produce a corresponding increase in retention through micromechanical friction . This may explain the increased retention of Lm on 20° angled implants after wear simulation.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Ortegon et al found a significant reduction in retention after wear for 20° implant angulations. The decreased retention of Le and Ll during anterior dislodging when implant angulation increases may be due to deterioration and wear of the central projection of these inserts more than the outer retentive ring . This wear increases as the angle of implant inclination increases …”
Section: Discussionmentioning
confidence: 99%
“…The existing evidence base describing retention differentials across interimplant differences is limited, with the majority of the precedent literature focusing on the retentive characteristics of locators on arbitrary or fixed interimplant distances only. 4,20,22 Only a single study has described the effect of interimplant distance on the retentive features of attachment systems 25 ; however, this study did not investigate the influence of the locator attachment itself. The results of the present study demonstrated that interimplant distance was associated with the initial retention of 3i locator attachments.…”
Section: Discussionmentioning
confidence: 79%
“…12,20 In addition, retention could be one of the most serious factors in determining patient satisfaction. 21,22 According to Caldwell,23 to masticate sticky foods, a distal extension removable partial denture requires a retaining force of 15 to 20 N. For normal foods, this force could be reduced to 10 N. Therefore, to maintain a denture in position, a retentive capacity of 10 to 20 N is necessary. 24 The functional masticatory forces in addition to forces generated by the insertion and removal of the overdenture cause micro-and macro-movement between the retentive parts of the attachment and can result in wear and the loss of retention over time.…”
Section: Jcdpmentioning
confidence: 99%
“…[12][13][14] Despite these promising studies, frequent maintenance requirements of ball attachments continues to be a challenge for clinicians. 16 Retention of a ball attachment system arises through mechanical interlocking and frictional contact due to attraction between the patrix and matrix. 9 Although it has been shown that such a retention force as low as 5-7 N is sufficient to stabilize implant overdentures in clinical use, 15 implant overdenture performance depends mainly on the retention force of the employed attachment system.…”
mentioning
confidence: 99%